Pengaruh Penggunaan Media Puzzle Terhadap Kemampuan Membaca Permulaan di Kelas II SDN 11 Pontianak Kota - Azza Nabila; Kartono Kartono; Siti Halidjah (Departement of Mathematics Education, 2024)
This research aims to test the effect of using puzzle media on early reading skills in class II SDN 11 Pontianak City. The research method used is an experimental method with a quasi-experimental design, with a nonequivalent control group design. The population in this study were all students in class II SDN 11 Pontianak City. The sample was determined using a saturated sampling technique and obtained a sample of class II A totaling 29 students as the experimental class and II totaling 29 students as the control class. The data collection technique used a measurement technique. The data collection tool used was an early reading test. Based on the data analysis, the average learning outcome of the experimental class was 83.40 and the average learning outcome of the control class was 71.24. The t-test results obtained tribune 5.67 and the table value of 2.003 because in determining the level of significance a = 0.05, a two-tailed test was carried out, then the value of a / 2 = 0.05 / 2 = 0.025 and degrees of freedom (dk) = k-2 = (29 + 29) – 2 = 56, then Ha is accepted. So it can be concluded that there is an influence of the use of puzzle media on the ability to read early in class II SDN 11 Pontianak City. From the effect size (ES), an ES of 1.38 was obtained (high criteria). This means that puzzle media has a high influence on the ability to read early in class li SDN 11 Pontianak City.